2016
DOI: 10.20944/preprints201609.0066.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of Antibody Titre of Dogs Vaccinated against Canine Distemper in Jos, Plateau State

Abstract: Determination of antibody titre of dogs vaccinated against canine distemper in Jos North and South local Government Areas of Plateau State was carried out by collection of sera of vaccinated dogs and administration of well-structured questionnaires to dog owners. The samples collected were analyzed using the immune-blot ELISA Kit to determining the antibody titre (immunoglobulin G). It indicated that dogs vaccinated against the disease mounted adequate protective immunity. The result revealed that 54 (90.0%) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
3
1
0
Order By: Relevance
“…In addition, the results of the third vaccination are in agreement with the study of Ogbu et al (2017) who investigated on vaccinating dogs against CDV. They showed that the third vaccine had significantly improved the performance of immunization (Ogbu et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition, the results of the third vaccination are in agreement with the study of Ogbu et al (2017) who investigated on vaccinating dogs against CDV. They showed that the third vaccine had significantly improved the performance of immunization (Ogbu et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…The results of comparing the performance of the two vaccines in this study are similar to the study by Ogbu et al (2017). They compared two vaccines made in Brazil and in the United States.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations